Curve sprinting in soccer: relationship with linear sprints and vertical jump performance - Loturco, Irineu; Pereira, Lucas A.; Fílter, Alberto; Olivares-Jabalera, Jesús; Reis, Valter P.; Fernandes, Victor; Freitas, Tomás T.; Requena, Bernardo (Biology of Sport, 2020)
ABSTRACT: We examined the relationships among linear speed, vertical jumping ability and curve sprint (CS) performance. Moreover, the correlations between linear and curvilinear sprint velocities and CS deficit were tested. Twenty-eight under-20 soccer players performed squat and countermovement jumps, 17-m linear sprint (with split times at 5 and 10 m), and a CS test for both sides. For the first time, the new proposed CS deficit was calculated as the difference between 17-m velocity and CS test velocity. Pearson’s product moment of correlation was performed to determine the relationships among the distinct variables tested. Significance level was set at P < 0.05. Large to very large relationships between linear sprint speed and CS performance were observed, on both the “good” and “weak” sides. In addition, moderate to large correlations between linear and curve sprint abilities and vertical jumps were found. Finally, the CS deficit was negatively associated with the CS good side performance. Linear sprint and CS velocities for both good and weak sides were closely related. The CS deficit was only related to the CS weak side performance, and the vertical jumping ability was significantly associated with both linear and curvilinear sprint velocities. The present results suggest that training methods capable of improving linear sprint and vertical jumping abilities may also improve CS performance.